Electrically Controllable Actuators Based on Supramolecular Peptide Hydrogels. (18th November 2016) - Xue, Bin; Qin, Meng; Wang, Tiankuo; Wu, Junhua; Luo, Dongjun; Jiang, Qing; Li, Ying; Cao, Yi; Wang, Wei
Abstract : Hydrogel actuators that can undergo structural change upon external stimuli are highly demanded due to their potential applications in diverse fields. However, the actuators based on physically cross‐linked supramolecular hydrogels are largely unexplored. This study reports the engineering of an electrically controllable supramolecular hydrogel as an actuator from a self‐assembling short peptide, in which a catechol moiety is introduced as the stimuli‐responsive motif. This kind of electrochemically responsive hydrogel is mechanically stable and can switch its physical properties dramatically upon the applied electric field. The mechanism and reversibility of the change are studied in detail. As a proof of principle, devices are designed to perform the unidirectional expansion and rotational motion under electrical stimulations. The applications of the actuators for controllable drug release and actuation of microfluidic devices are also illustrated. It is expected that these kind of supramolecular hydrogel actuators can find broad applications as novel biosensors, artificial robots, and smart soft materials. Abstract : Electrically controllable hydrogels have been used as biomimetic actuators in diverse fields . However, these hydrogels are mainly made of ionic polymers and the supramolecular hydrogels for actuators are yet to be demonstrated. Here this study shows the possibility of using redox responsive peptide hydrogels as electrically sensitive units for various actuators. The applications of the actuators are also illustrated.